The Stability of Roadway Groups under Rheology Coupling Mining Disturbance - Sen Yang (MDPI AG, 2021)
The deep roadway groups play an important role in transportation and ventilation in coal mine production. Therefore, it is very important to comprehensively analyze the coupling effect of rheological deformation and coal mining on the stability of the roadway groups. In this paper, the disturbance effects of different stop-mining lines on roadway groups under long-term rheology were investigated by numerical simulation, and the failure mechanism of roadway groups with large sections and multiple disturbances in a deep well was revealed. The results show that the long working face will lead to the collapse of key strata, and the influence range will spread to the adjacent roadway groups. When the distance between the working face and the stop-mining line is 100 m, the roadway groups cannot be affected by the working face mining, and the reserved width of the coal pillar can be determined to be 100 m, which increases the stability of the roadway’s surrounding rock and maintains the mine safety production. This paper aims to provide a reference for groups design and control under similar conditions.